2021
DOI: 10.1126/science.abj2949
|View full text |Cite
|
Sign up to set email alerts
|

Profiling cellular diversity in sponges informs animal cell type and nervous system evolution

Abstract: Sponges and evolutionary origins Sponges represent our distant animal relatives. They do not have a nervous system but do have a simple body for filter feeding. Surveying the cell types in the freshwater sponge Spongilla lacustris , Musser et al . found that many genes important in synaptic communication are expressed in cells of the small digestive chambers. They found secretory machinery characteristic of the presynapse in small multipola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
143
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 89 publications
2
143
0
1
Order By: Relevance
“…Cellular immunity by phagocytosis is the most ancient and widespread mechanism among basal Metazoa. For example, in sponges and cnidarians, the encapsulation is carried out by amoebocytes (=archeocytes) or collencytes ( Musser et al, 2021 ). Phagocytosis in invertebrates, like in vertebrates, includes several stages: chemotaxis, recognition, attachment of a foreign agent to the phagocyte membrane, intracellular lysis, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular immunity by phagocytosis is the most ancient and widespread mechanism among basal Metazoa. For example, in sponges and cnidarians, the encapsulation is carried out by amoebocytes (=archeocytes) or collencytes ( Musser et al, 2021 ). Phagocytosis in invertebrates, like in vertebrates, includes several stages: chemotaxis, recognition, attachment of a foreign agent to the phagocyte membrane, intracellular lysis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Early (and present) animals strongly depended on the environmental and symbiotic bacteria, and fiber-type cells (or similar/homologous classes of amoebocytes as recently described in sponges - Musser et al, 2021 ) might be critical elements in the shared evolution of immune and neural systems to integrate both morphogenesis and behaviors ( Fields et al, 2020 ). Here, the defense against bacterial infections can be an inherent part of such integrative ancestral adaptive responses.…”
Section: Discussionmentioning
confidence: 99%
“…The control of multicellular behavior by NO/cCMP signaling in C. flexa is reminiscent of its function in animals, most notably in sponges 47 . In the demosponges Tethya wilhelma 15 , Ephydatia muelleri 13 , and Spongilla lacustris 14 , NO induces global contractions and stops flagellar beating in choanocyte chambers, which interrupts feeding, allows expulsion of clumps of waste, and flushes the aquiferous canal system (a behavior sometimes called "sneezing") 48 . Recently, single-cell RNA sequencing in Spongilla lacustris revealed that pinacocytes (epithelial cells that cover and shape the sponge body) co-express NOS and sGC 14,49 , the actomyosin contractility module and the transcription factor Serum response factor (Srf), a master regulator of contractility 14,50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…The NO/cGMP pathway acts independently from other inducers of C. flexa contraction, including mechanical stimuli and heat, but sGC activity is required for contractions induced by light-to-dark transitions. The output of NO signaling in C. flexa – contractions resulting in a switch from feeding to swimming – resembles the effect of NO in sponges 1-3 and cnidarians 11,16,17 , where it interrupts feeding and activates contractility. These data provide insights into the biology of the first animals and the evolution of NO signaling.…”
mentioning
confidence: 99%
“…), and data analysis techniques used. Indeed, scSeq projects have been performed on diverse organisms such as lizards [ 5 ], ants [ 6 ], fish [ 7 ], sponges [ 8 ], and flatworms [ 9 , 10 ]. Svensson et al maintains a curated database of scSeq studies which can be filtered by organism and tissue type [ 11 ].…”
Section: Considerations When Planning a Scseq Study In Non-model Orga...mentioning
confidence: 99%